Neuroprotective effect of loganin against Aβ25–35-induced injury via the NF-κB-dependent signaling pathway in PC12 cells. Issue 4 (17th March 2015) - Kim, Hyeri; Youn, Kumju; Ahn, Mok-Ryeon; Kim, Oh Yoen; Jeong, Woo-Sik; Ho, Chi-Tang; Jun, Mira
Abstract : Aβ25–35 -induced neurotoxicity was ameliorated by the inhibition of the NF-κB dependent signaling pathway. Abstract : Amyloid-beta (Aβ) protein, the main constituent of senile plaques, is believed to play a pivotal role in the pathogenesis of Alzheimer's disease (AD). AD is closely associated with inflammatory reactions which are considered to be responses to Aβ deposition. The present study investigated the effect of loganin on Aβ25–35 -induced inflammatory damage and the underlying molecular mechanism of its neuroprotective action. Loganin predominantly prevented Aβ25–35 -stimulated cell death through suppressing ROS generation, and attenuating apoptosis by inhibiting caspase-3 activity and regulating cell cycle. Furthermore, loganin suppressed the level of TNF-α and protein expression of iNOS and COX-2 in Aβ25–35 -injured PC12 cells. These inhibitions appeared to correlate with the suppression of NF-κB activation by loganin, as pre-treating cells with loganin blocked the translocation of NF-κB into the nuclear compartment and degradation of the inhibitory subunit IκB. Loganin substantially inhibited phosphorylation of MAPKs including ERK1/2, p38 and JNK, which are closely related to regulation of NF-κB activation. Taken together, the results implied that loganin attenuated neuroinflammatory responses through the inactivation of NF-κB by NF-κB dependent inflammatory pathways and phosphorylation of MAPK in Aβ25–35 -induced PC12 cells.